2003
DOI: 10.1002/j.2333-8504.2003.tb01922.x
|View full text |Cite
|
Sign up to set email alerts
|

What Is Quantitative Reasoning? Defining the Construct for Assessment Purposes

Abstract: In order to create fair and valid assessments, it is necessary to be clear about what is to be measured and how the resulting data should be interpreted. For a number of historical and practical reasons described in this paper, adequately detailed statements with both a theoretical and empirical base do not currently exist for the construct of quantitative reasoning for use in assessments. There is also no adequate explanation of the important differences between assessments that measure quantitative reasoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
0
21
0
11
Order By: Relevance
“…For example, Dwyer et al (2003) defined quantitative reasoning as "the ability to analyze quantitative information" (p. 13) and specified that its domain would be restricted to quantitative tasks that would be new to the student (i.e., would not require methods that the test takers had been taught). They suggested that quantitative reasoning includes six more specific capabilities: (a) understanding quantitative information presented in various formats, (b) interpreting and drawing inferences from quantitative information, (c) solving novel quantitative problems, (d) checking the reasonableness of the results, (e) communicating quantitative information, and (f) recognizing the limitations of quantitative methods.…”
Section: Adequate Sampling Of the Traitmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dwyer et al (2003) defined quantitative reasoning as "the ability to analyze quantitative information" (p. 13) and specified that its domain would be restricted to quantitative tasks that would be new to the student (i.e., would not require methods that the test takers had been taught). They suggested that quantitative reasoning includes six more specific capabilities: (a) understanding quantitative information presented in various formats, (b) interpreting and drawing inferences from quantitative information, (c) solving novel quantitative problems, (d) checking the reasonableness of the results, (e) communicating quantitative information, and (f) recognizing the limitations of quantitative methods.…”
Section: Adequate Sampling Of the Traitmentioning
confidence: 99%
“…That is, broadly defined traits that are of practical interest may involve a number of more narrowly defined traits or factors that contribute to the test taker's performance. For example, as noted earlier, Dwyer et al (2003) defined the performance domain for quantitative reasoning in terms of six capabilities, including understanding quantitative information, interpreting quantitative information, solving quantitative problems, and estimating and checking answers for reasonableness. In addition, most trait measures require ancillary abilities (e.g., the ability to read) that are needed for effective performance in the assessment context.…”
Section: Factor Analysismentioning
confidence: 99%
“…Development of an operational or construct definition is “essential to validity and fairness to the scientific integrity of the inferences drawn from assessments” and helps to aid “decision‐making about assessment design, development, and interpretation” (Dwyer et al, , p. 1). Based on a synthesized review of the frameworks and definitions by national and international organizations, workforce initiatives, higher educational institutions and researchers, and K–12 theorists and practitioners, as well as existing assessments measuring quantitative literacy skills, we propose an operational definition for a next‐generation quantitative literacy assessment.…”
Section: Proposing a Next‐generation Quantitative Literacy Assessmentmentioning
confidence: 99%
“…Dwyer et al () noted that to solve quantitative reasoning problems, mathematical content knowledge is needed. After examining and synthesizing the quantitative literacy literature and existing assessments, we identified four content areas important for assessing quantitative literacy in a higher education context: (a) number and operations, (b) algebra, (c) geometry and measurement, and (d) probability and statistics (see Table ).…”
Section: Proposing a Next‐generation Quantitative Literacy Assessmentmentioning
confidence: 99%
“…Estas capacidades permiten ejemplificar aún más que la habilidad cuantitativa no es conocimiento matemático, sino la habilidad asociada a la comprensión de la información cuantitativa (Dwyer, Gallagher, Levin y Morley, 2003). Siguiendo a estos autores, el razonamiento cuantitativo es "la capacidad de analizar la información cuantitativa, incluyendo la determinación de qué técnicas y procedimientos se pueden aplicar a un problema particular para llegar a su solución" (2003: 12); ellos hacen énfasis en que el razonamiento cuantitativo no se refiere a las habilidades de cálculo, sino a la capacidad para determinar cuál es la mejor estrategia de cálculo para resolver un problema y a la habilidad de inferir el grado de precisión requerido para estos cálculos.…”
Section: )unclassified